Separator for electrochemical element
Patent Information
- Application Number
- JP2024204347
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-25
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-26
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
【0009】 本発明によれば、セパレータの強度を維持しつつ、薄葉化可能な電気化学素子用セパレータを提供できる。
Smart Images

Figure 2025026997000002 
Figure 2025026997000003 
Figure 2025026997000004
Abstract
Description
[Technical field]
[0001] This patent application claims priority under the Paris Convention to Japanese Patent Application No. 2019-234225 (filing date: December 25, 2019), the entire contents of which are incorporated herein by reference. The present invention relates to a separator for an electrochemical element suitable for an electrochemical element, and an electrochemical element including the separator. [Background technology]
[0002] Electrochemical elements such as capacitors are capable of charging and discharging large currents, and have long lifespans with little performance degradation due to repeated charging and discharging. In addition to applications such as backup power sources for small products such as mobile phones and smartphones, in recent years they have also been put to practical use and are being considered for applications such as storing and stabilizing power, power assist, backup power sources, and energy regeneration for large products such as automobiles, digital multi-function printers, and vending machines.
[0003] In such an electrochemical element, a separator is used to separate the positive and negative electrodes. For example, Patent Document 1 discloses a separator for an electrochemical element made of a wet-laid nonwoven fabric containing, as essential components, synthetic short fibers and solvent-spun cellulose fibers having a specific modified freeness and a specific length-weighted average fiber length. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2012-222266 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, there has been a demand for thinner separators in electrochemical elements to reduce their capacity in order to further improve the performance of electrochemical elements and to reduce the size and / or weight of the electrochemical elements. However, according to the studies of the present inventors, it has been found that it is difficult to thin the conventional separators described in the above documents without reducing the weight per unit area, and that thinning the separator reduces the weight per unit area, which reduces the strength of the separator and may cause problems such as reduced strength, durability, etc. of the electrochemical element.
[0006] SUMMARY OF THE PRESENT DISCLOSURE An object of the present invention is to provide a separator for an electrochemical element that can be made thinner while maintaining the strength of the separator. [Means for solving the problem]
[0007] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention provides the following preferred embodiments.
[0008] [1] A separator for an electrochemical element comprising synthetic fibers and beaten cellulose fibers, The Canadian standard freeness of the beaten cellulose fiber, measured in accordance with JIS P 8121, is 50 ml or more and 500 ml or less; In the fiber diameter distribution histogram of the beaten cellulose fiber, (1) the fiber has a maximum frequency peak in the range of 50 μm or less; (2) The proportion of the fibers having a fiber diameter of 20 μm or less is 55% or more; Separator for electrochemical elements. [2] The separator for an electrochemical element according to [1], further comprising a binder. [3] The separator for an electrochemical element according to [1] or [2], wherein in a fiber diameter distribution histogram of the beaten cellulose fibers, the proportion of said fibers having a fiber diameter of more than 30 μm is 10% or less. [4] The separator for an electrochemical element according to any one of [1] to [3], wherein the synthetic fiber is a polyvinyl alcohol-based fiber and / or a polyester-based fiber. [5] The separator for an electrochemical element according to any one of [1] to [4], wherein the beaten cellulose fibers are natural cellulose fibers obtained by beating. [6] The separator for an electrochemical element according to any one of [2] to [5], wherein the binder is a polyvinyl alcohol-based binder. [7] The separator for an electrochemical element according to any one of [1] to [6], wherein the content of the synthetic fiber is 1% by mass or more and 55% by mass or less based on the total mass of the separator. [8] The separator for an electrochemical element according to any one of [1] to [7], wherein the content of the beaten cellulose fibers is 30% by mass or more and 95% by mass or less based on the total mass of the separator. [9] The separator for an electrochemical element according to any one of [2] to [8], wherein the content of the binder is 0.5 mass % or more and 20 mass % or less based on the total mass of the separator.
[10] The separator for an electrochemical element according to any one of [1] to [9], which has a thickness of 10 μm or more and less than 70 μm.
[11] An electrochemical element comprising the separator for an electrochemical element according to any one of [1] to
[10] . Effect of the Invention
[0009] According to the present invention, it is possible to provide a separator for an electrochemical element that can be made thinner while maintaining the strength of the separator. [Brief description of the drawings]
[0010] [Figure 1] FIG. 1 is a fiber diameter distribution histogram of natural cellulose fibers with a freeness of 25 ml. [Diagram 2] FIG. 2 is a fiber diameter distribution histogram of natural cellulose fibers with a freeness of 150 ml. [Diagram 3] FIG. 3 is a fiber diameter distribution histogram of natural cellulose fibers with a freeness of 250 ml. [Figure 4] FIG. 4 is a fiber diameter distribution histogram of natural cellulose fibers with a freeness of 350 ml. [Diagram 5] FIG. 5 is a fiber diameter distribution histogram of natural cellulose fibers with a freeness of 550 ml. [Figure 6] FIG. 6 is a fiber diameter distribution histogram of organic solvent-based cellulose fibers with a freeness of 50 ml. [Figure 7] FIG. 7 is a fiber diameter distribution histogram of organic solvent-based cellulose fibers with a freeness of 250 ml. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] [Separators for electrochemical elements] The separator for electrochemical elements of the present invention (hereinafter, simply referred to as "separator") contains synthetic fibers and beaten cellulose fibers. The beaten cellulose fibers have a Canadian Standard Freeness of 50 ml to 500 ml, and in a fiber diameter distribution histogram of the beaten cellulose fibers, (1) the fibers have a maximum frequency peak in the range of 50 μm or less, and (2) the proportion of the fibers having a fiber diameter of 20 μm or less is 55% or more.
[0012] <Synthetic fibers> The separator of the present invention has high strength because it contains synthetic fibers.
[0013] Examples of synthetic fibers include polyvinyl alcohol fibers, ethylene-vinyl alcohol copolymer fibers, polyester fibers, polypropylene fibers, polyethylene fibers, polypropylene-polyethylene composite fibers, polyamide fibers, polyamide-modified polyamide composite fibers, etc. These may be used alone or in combination of two or more. Among these, from the viewpoint of easily increasing the strength of the separator, preferred synthetic fibers are polyvinyl alcohol-based fibers and polyester-based fibers, and from the viewpoint of easily making the separator thinner and easily obtaining a separator with low resistance, polyvinyl alcohol-based fibers are more preferred.
[0014] The vinyl alcohol polymer constituting the polyvinyl alcohol fiber is not particularly limited, and may be, for example, a vinyl alcohol polymer having an average degree of polymerization of 1000 to 5000 and a degree of saponification of 95 mol% or more. The vinyl alcohol polymer may be a homopolymer of vinyl alcohol or a copolymer of vinyl alcohol and another copolymer component. When the vinyl alcohol polymer contains another copolymer component, the proportion of the copolymer component in the vinyl alcohol polymer is preferably 20 mol% or less, more preferably 10 mol% or less, from the viewpoint of water resistance, etc. In addition, the vinyl alcohol polymer may be subjected to a treatment such as acetalization, if necessary.
[0015] In the present invention, the polyvinyl alcohol-based fiber as a synthetic fiber may be composed of only a vinyl alcohol-based polymer, or may be a composite spun fiber of a vinyl alcohol-based polymer and another polymer, a mixed spun fiber (sea-island fiber), etc. The proportion of the polyvinyl alcohol-based polymer in the polyvinyl alcohol-based fiber is preferably 30% by weight or more, more preferably 50% by weight or more, and even more preferably 80% by weight or more, based on the total weight of the polyvinyl alcohol-based fiber, from the viewpoints of electrolyte absorption and strength. The upper limit of the proportion is not particularly limited, and may be, for example, 100% by weight or less.
[0016] The polyvinyl alcohol-based synthetic fiber is preferably heat-treated from the viewpoint of the heat resistance of the separator. The heat treatment temperature is not particularly limited and may be, for example, 60° C. or more and 210° C. or less. The heat treatment time is not particularly limited and may be, for example, 1 second or more and 30 minutes or less.
[0017] In one embodiment of the present invention, the number average fiber diameter of the synthetic fibers is preferably 0.1 μm or more, more preferably 0.5 μm or more, and even more preferably 1.0 μm or more, from the viewpoint of the shielding properties of the separator. Also, from the viewpoint of easily thinning the separator, it is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. The number average fiber diameter of the synthetic fibers can be measured using a "Fiber Tester" manufactured by Lorentzen & Wettre.
[0018] In one embodiment of the present invention, the fineness of the synthetic fiber is preferably 0.1 dtex or more, more preferably 0.2 dtex or more, from the viewpoint of the shielding property (air permeability) of the separator. Also, from the viewpoint of easily thinning the separator (easiness to obtain a thin separator), it is preferably 1.0 dtex or less, more preferably 0.8 dtex or less, and even more preferably 0.6 dtex or less. The fineness of the synthetic fiber can be measured by an optical microscope or an electron microscope (SEM).
[0019] The cross-sectional shape of the synthetic fibers may be, for example, circular, elliptical, cocoon-shaped, flat, etc., and from the viewpoint of facilitating the thinning of the separator, the cocoon-shaped shape is preferred.
[0020] In a preferred embodiment of the present invention, from the viewpoint of easily increasing the strength of the separator, the content of synthetic fibers is 1% by mass or more and 55% by mass or less with respect to the total mass of the separator. Moreover, from the viewpoint of easily increasing the strength of the separator, the content of synthetic fibers is more preferably 5% by mass or more, even more preferably 10% by mass or more, and particularly preferably 15% by mass or more with respect to the total mass of the separator. Moreover, from the viewpoint of easily thinning the separator, the content of synthetic fibers is more preferably 50% by mass or less, even more preferably 40% by mass or less, and particularly preferably 30% by mass or less with respect to the total mass of the separator.
[0021] <Beaten cellulose fiber> The separator of the present invention contains beaten cellulose fibers having a specific freeness and a specific fiber diameter distribution, and thus the separator can be easily thinned without decreasing the basis weight, so that it is possible to maintain high strength while thinning the separator. The beaten cellulose fibers refer to cellulose fibers that have been beaten.
[0022] The Canadian standard freeness of the beaten cellulose fiber in the present invention, measured according to JIS P 8121, is 50 ml or more and 500 ml or less. If the freeness is outside the above range, it is difficult to ensure the function as a separator. Specifically, if the freeness is less than the above lower limit, the air permeability of the separator is excessively reduced, and the resistance value is likely to increase, and if the freeness exceeds the above upper limit, the air permeability is excessively increased, and the shielding property is likely to decrease. If the freeness exceeds the above upper limit, it is difficult to thin the separator. In addition, the freeness is preferably 100 ml or more, more preferably 150 ml or more, and even more preferably 200 ml or more, from the viewpoint of easily increasing the strength and shielding property of the separator. In addition, the freeness is preferably 400 ml or less, more preferably 350 ml or less, and even more preferably 300 ml or less, from the viewpoint of easily thinning the separator and easily reducing the resistance value. The freeness can be adjusted by the degree of beating of the beaten cellulose fibers and the method of beating the cellulose fibers.
[0023] The beaten cellulose fiber in the present invention has a maximum frequency peak in the range of 50 μm or less in a fiber diameter distribution histogram of the beaten cellulose fiber. If the range having the maximum frequency peak exceeds the upper limit, it is difficult to maintain the strength of the separator while thinning the separator, and it is difficult to obtain a thin separator having high strength. In one embodiment of the present invention, from the viewpoint of easily obtaining a thinner separator, the upper limit of the range having the maximum frequency peak is preferably 40 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less. The lower limit of the range is not particularly limited from the viewpoint of easily thinning the separator, and may usually be more than 0 μm. From the viewpoint of easily reducing the resistance of the separator, it is preferably 6 μm or more, more preferably 10 μm or more, and even more preferably 14 μm or more.
[0024] The fiber diameter distribution histogram of the beaten cellulose fibers is created using the fiber diameter data of the beaten cellulose fibers. The fiber diameter data used to create the histogram is obtained by first dispersing 100 g of beaten cellulose fiber in 10 L of water to prepare a slurry, and then measuring the fiber diameter of the beaten cellulose fiber using the prepared slurry with a "Fiber Tester" manufactured by Lorentzen & Wettre, for example, by the method described in the Examples.
[0025] In the present invention, the class width of the fiber diameter histogram of the beaten cellulose fiber may be appropriately set depending on the analytical device, etc. so as to be able to confirm whether or not the fiber has the desired fiber diameter, and is preferably 10 or less, more preferably 5 or less, even more preferably 3 or less, and particularly preferably 2 or less.
[0026] In the present invention, the maximum frequency peak in a fiber diameter distribution histogram refers to the most frequent class (or data interval) in the fiber diameter distribution histogram. When there are two or more most frequent classes in a histogram, the class that contains the larger fiber diameter among the most frequent classes is regarded as the maximum frequency peak. The maximum frequency peak can be adjusted by the freeness and type of the beaten cellulose fibers.
[0027] The beaten cellulose fiber in the present invention further has a fiber diameter distribution histogram in which the proportion of the fibers having a fiber diameter of 20 μm or less is 55% or more. If the proportion is less than the lower limit, it is difficult to maintain the strength of the separator while thinning the separator. In one embodiment of the present invention, the proportion is preferably 60% or more, more preferably 63% or more, and even more preferably 65% or more, from the viewpoint of easily obtaining a thinner separator. In the present invention, the proportion of the fibers having a fiber diameter of 20 μm or less in the fiber diameter distribution histogram means the proportion ((total frequency of frequencies of 20 μm or less / total frequency)×100) of the sum of frequencies (total frequency) of all classes (all data intervals) in the fiber diameter distribution histogram. For example, when the class width of the fiber diameter distribution histogram is 2, the ratio is the ratio of the sum of the frequencies from the class including the minimum fiber diameter to the class of 20 μm or more and less than 22 μm (total frequency of frequencies of 20 μm or less) to the sum of the frequencies of all classes of the fiber diameter distribution histogram (total frequency) ((total frequency of frequencies of 20 μm or less / total frequency)×100).
[0028] In one embodiment of the present invention, from the viewpoint of easily achieving both the maintenance of separator strength and the thinning of the separator, the beaten cellulose fiber preferably has a ratio of fibers having a fiber diameter of 30 μm or less in a fiber diameter distribution histogram of the beaten cellulose fiber of 90% or more, more preferably 92% or more, and even more preferably 95% or more. In the present invention, the ratio of the fibers having a fiber diameter of 30 μm or less in a fiber diameter distribution histogram means the ratio ((total frequency of frequencies of 30 μm or less / total frequency)×100) of the total frequency (total frequency) of all classes (all data intervals) in the fiber diameter distribution histogram. For example, when the class width of the fiber diameter distribution histogram is 2, the ratio is the ratio of the sum of the frequencies from the class including the minimum fiber diameter to the class of 30 μm or more and less than 32 μm (total frequency of 30 μm or less) to the sum of the frequencies of all classes (total frequency) ((total frequency of 30 μm or less / total frequency)×100).
[0029] The higher the ratio of the fibers having a diameter of 20 μm or less and the ratio of the fibers having a diameter of 30 μm or less, the easier it is to make the separator thinner. Therefore, the upper limit is not particularly limited and may be 100% or less.
[0030] In a preferred embodiment of the present invention, from the viewpoint of easily achieving both the maintenance of separator strength and the thinning of the separator, the ratio of fibers having a fiber diameter of more than 30 μm in a fiber diameter distribution histogram of the beaten cellulose fibers of the present invention is 10% or less, more preferably 8% or less, and even more preferably 5% or less. The ratio of fibers having a fiber diameter of more than 30 μm in a fiber diameter distribution histogram means the ratio ((total frequency of fibers having a fiber diameter of more than 30 μm / total frequency)×100) of the total frequency (total frequency) of all classes (all data intervals) in the fiber diameter distribution histogram. For example, when the class width of the fiber diameter distribution histogram is 2, the ratio means the ratio of the sum of the frequencies from the class of 32 μm or more and less than 34 μm to the class including the maximum fiber diameter (total frequency) to the sum of the frequencies of all classes (total frequency) ((total frequency of 32 μm or more / total frequency)×100). The lower the ratio of fibers having a fiber diameter of more than 30 μm, the easier it is to thin the separator. Therefore, the lower limit is not particularly limited and may be 0%.
[0031] The respective proportions of fibers having diameters of 20 μm or less, 30 μm or less, and more than 30 μm in the fiber diameter distribution histogram of the beaten cellulose fibers can be adjusted depending on the freeness of the beaten cellulose fibers and their type.
[0032] The number average fiber diameter of the beaten cellulose fibers is preferably 20 μm or less, more preferably 19 μm or less, and even more preferably 18.5 μm or less, from the viewpoint of easily making the separator thinner, and is preferably 10 μm or more, more preferably 13 μm or more, and even more preferably 15 μm or more, from the viewpoint of easily reducing the resistance value of the separator.
[0033] The maximum fiber diameter of the beaten cellulose fibers is preferably 70 μm or less, more preferably 69 μm or less, and even more preferably 67 μm or less, from the viewpoint of easily making the separator thinner, and is preferably 40 μm or more, more preferably 50 μm or more, and even more preferably 55 μm or more, from the viewpoint of easily reducing the resistance value of the separator.
[0034] The minimum fiber diameter of the beaten cellulose fibers is preferably 1 μm or more, more preferably 3 μm or more, and even more preferably 6 μm or more, from the viewpoint of easily reducing the resistance value of the separator, and is preferably 15 μm or less, more preferably 14 μm or less, and even more preferably 12 μm or less, from the viewpoint of easily making the separator thinner.
[0035] The number average fiber diameter, maximum fiber diameter, and minimum fiber diameter of the beaten cellulose fiber can be adjusted by the freeness and type of the beaten cellulose fiber, etc. These fiber diameters can be calculated from the fiber diameter measured using a "Fiber Tester" manufactured by Lorentzen & Wettre.
[0036] In the present invention, the beaten cellulose fiber is not particularly limited as long as it has a freeness of 50 ml to 500 ml, a fiber diameter histogram of the fiber has a maximum frequency peak in the range of 50 μm or less, and the proportion of the fiber having a fiber diameter of 20 μm or less is 55% or more. For example, the beaten cellulose fiber may be a natural cellulose fiber obtained by beating, an organic solvent-based cellulose fiber obtained by beating, or a mixture thereof. The organic solvent-based cellulose fiber is a cellulose fiber (lyocell) obtained by an organic solvent spinning method in which cellulose is directly dissolved without a derivative and spun.
[0037] In a preferred embodiment of the present invention, the beaten cellulose fibers are natural cellulose fibers that have been beaten in order to facilitate thinning of the separator. The organic solvent-based cellulose fibers are beaten to form fibers having a thick trunk portion and thin branches extending from the thick trunk portion, and the thick trunk portion has a fiber diameter similar to that of the fiber before beating. In contrast, natural cellulose fibers are less likely to form a thick trunk portion, as occurs when organic solvent-based cellulose fibers are beaten, and therefore the fiber diameter is easily reduced by beating. Therefore, the natural cellulose fibers are more likely to reduce the upper limit of the range having the maximum frequency peak in the histogram of beaten cellulose fibers (e.g., 50 μm or less) and to increase the proportion of fibers having a fiber diameter of 20 μm or less (e.g., 55% or more), and therefore thinner separators can be easily obtained by using the natural cellulose fibers.
[0038] Since the use of natural cellulose fibers as the beaten cellulose fibers makes it easier to make the separator thinner, the content of the natural cellulose fibers is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 90% by mass or more, based on the total mass of the beaten cellulose fibers. The upper limit of the content is not particularly limited, and may be, for example, 100% by mass or less.
[0039] Examples of natural cellulose fibers include wood pulp such as softwood pulp and hardwood pulp, cotton linter pulp, and hemp pulp, and wood pulp is preferred. These natural cellulose fibers may be used alone or in combination of two or more. In addition, the natural cellulose fibers are preferably mercerized from the viewpoint of the dimensional stability of the separator.
[0040] The cross-sectional shape of the beaten cellulose fibers may be, for example, a circular shape, an elliptical shape, a cocoon shape, a flat shape, or the like, and from the viewpoint of facilitating the thinning of the separator, a flat shape is preferable.
[0041] Beaten cellulose fibers can be prepared by beating cellulose fibers such as natural cellulose fibers, organic solvent-based cellulose fibers, etc. The method for beating cellulose fibers is not particularly limited, and may be, for example, according to JIS P-8221-1-98.
[0042] In a preferred embodiment of the present invention, from the viewpoint of easily thinning the separator, the content of the beaten cellulose fibers is 30% by mass or more and 95% by mass or less with respect to the total mass of the separator. Moreover, from the viewpoint of easily thinning the separator, the content of the beaten cellulose fibers is more preferably 50% by mass or more, even more preferably 60% by mass or more, and particularly preferably 70% by mass or more. Moreover, from the viewpoint of easily increasing the strength of the separator, the content is more preferably 90% by mass or less, even more preferably 85% by mass or less, and particularly preferably 80% by mass or less.
[0043] <Other fibers> The separator of the present invention may contain other fibers, if necessary, in addition to the above-mentioned synthetic fibers and beaten cellulose fibers. The other fibers are not particularly limited as long as they do not impair the effects of the present invention, and examples thereof include cellulose fibers other than the beaten cellulose fibers of the present invention. When the separator contains other fibers, the content of the other fibers is not limited as long as it does not impair the effects of the present invention, and may be, for example, 0.1 mass% or more and 20 mass% or less with respect to the total mass of the separator. From the viewpoint of easily thinning the separator, the content of the other fibers is preferably 15 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less.
[0044] <Binder> In a preferred embodiment of the present invention, the separator of the present invention further contains a binder from the viewpoint of easily increasing the strength of the separator. The binder is not particularly limited, but is preferably one that can bond the fibers contained in the separator to each other. Examples of the binder include polyvinyl alcohol-based binders and ethylene-vinyl alcohol-based binders. Among them, polyvinyl alcohol-based binders are preferred from the viewpoint of easily increasing the strength of the separator.
[0045] The vinyl alcohol polymer constituting the polyvinyl alcohol binder may be the same as the vinyl alcohol polymer constituting the polyvinyl alcohol fiber as the synthetic fiber.
[0046] The raw material form of the binder contained in the separator is not particularly limited and may be, for example, a fibrous form, a powder form, a solution form, or the like. From the viewpoint of easily improving the adhesiveness between the fibers contained in the separator, a fibrous form is preferable.
[0047] When polyvinyl alcohol-based fibers are used as the polyvinyl alcohol-based binder raw material, the polyvinyl alcohol-based fibers may be the same as those described above as the synthetic fibers. However, from the viewpoint of easily improving the adhesiveness between the synthetic fibers and the beaten cellulose fibers, it is preferable that the polyvinyl alcohol-based fibers used as the binder raw material are not heat-treated.
[0048] In a preferred embodiment of the present invention, when the separator contains a binder, the content of the binder is 0.5% by mass or more and 20% by mass or less with respect to the total mass of the separator, from the viewpoint of easily increasing the strength of the separator. Moreover, from the viewpoint of easily increasing the strength of the separator and easily thinning the separator, the content of the binder is more preferably 1% by mass or more, even more preferably 2% by mass or more, and particularly preferably 3% by mass or more with respect to the total mass of the separator. Moreover, from the viewpoint of easily reducing the resistance value of the separator, the content of the binder is more preferably 15% by mass or less, even more preferably 10% by mass or less, and particularly preferably 8% by mass or less with respect to the total mass of the separator.
[0049] <Separators for electrochemical elements> In the present invention, since the separator contains synthetic fibers and beaten cellulose fibers having a specific freeness and a specific fiber diameter distribution, a separator having high strength and thinness can be obtained. The thickness of the separator of the present invention may be appropriately selected depending on the type of electrochemical element using the separator, and may be, for example, 10 μm or more and less than 70 μm. In addition, the thickness of the separator of the present invention is preferably 60 μm or less, more preferably 55 μm or less, and even more preferably 53 μm or less from the viewpoint of easily obtaining a separator that can improve the performance, reduce the size, and reduce the weight of the electrochemical element. In addition, the thickness of the separator is preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 35 μm or more from the viewpoint of easily increasing the strength of the separator. The thickness of the separator can be adjusted by the freeness and fiber diameter distribution of the beaten cellulose fibers, and the basis weight of the separator. The thickness of the separator can be measured according to JIS P 8118.
[0050] The basis weight of the separator of the present invention is preferably 10 g / m from the viewpoint of easily increasing the strength of the separator. 2 More preferably, 15 g / m 2 More preferably, 18 g / m 2 From the viewpoint of making the separator easier to thin, the thickness is preferably 30 g / m 2 Less than or equal to 25 g / m 2Less than 23 g / m, more preferably 23 g / m 2 The basis weight can be measured according to JIS P 8124.
[0051] The separator of the present invention contains synthetic fibers and beaten cellulose fibers having a specific freeness and a specific fiber diameter distribution, and therefore has high strength even though it is thin. The strength of the separator of the present invention is preferably 0.3 kg / 15 mm or more, more preferably 0.35 kg / 15 mm or more, and even more preferably 0.4 kg / 15 mm or more, from the viewpoint of easily improving the durability of the separator and the electrochemical element containing the separator. In addition, since the higher the strength, the higher the durability tends to be, the upper limit is not particularly limited and may be 1.0 kg / 15 mm or less. The strength can be adjusted by the content and basis weight of the synthetic fibers in the separator. The strength can be measured according to JIS P-8113 using a tensile tester.
[0052] The air permeability of the separator of the present invention is preferably 5.5 cc / cm from the viewpoint of easily reducing the resistance value of an electrochemical element including the separator. 2 / sec or more, more preferably 6.0cc / cm 2 / sec or more, more preferably 6.5cc / cm 2 / sec or more, and from the viewpoint of easily increasing the shielding property of the separator, it is preferably 20 cc / cm 2 / sec or less, more preferably 18cc / cm 2 / sec or less, and more preferably 15cc / cm 2 / sec or less. The air permeability of the separator can be adjusted by the freeness of the beaten cellulose fiber, the fiber composition of the separator (for example, the content ratio of synthetic fiber and beaten cellulose fiber in the separator), etc. The air permeability can be measured according to JIS L 1096 6.27.
[0053] From the viewpoint of practical use of the separator, the resistance of the separator of the present invention is preferably 3.0Ω or less, more preferably 2.8Ω or less, and even more preferably 2.5Ω or less. The resistance value of the separator can be adjusted by the freeness of the beaten cellulose fiber, the fiber composition contained in the separator, etc. The resistance value of the separator can be measured by a resistance measuring device, for example, by the method described in the Examples.
[0054] [Method of manufacturing separator for electrochemical element] The method for producing the separator of the present invention is not particularly limited, and the separator can be produced by a known papermaking method. For example, the separator can be produced by mixing synthetic fibers and beaten cellulose fibers, and optionally other fibers and / or binders, dispersing the mixture in water to prepare a slurry, and then carrying out papermaking using a general wet papermaking machine. Examples of the wire used in the papermaking machine include a cylinder, a short wire, and a fourdrinier wire. These wires may be used alone to form a single layer, or a combination of wires may be used to form a multi-layered paper. In order to obtain a homogeneous paper without unevenness and excellent electrical properties, it is preferable to form a multi-layered paper, and it is particularly preferable to form a two-layered paper using a short wire-cylinder papermaking machine. After the paper is made using a wet papermaking machine, it is dried using a Yankee dryer or the like to obtain the desired separator. In addition, heat pressing or the like may be performed as necessary. Furthermore, in order to improve the electrolyte absorption, a hydrophilic treatment such as a surfactant treatment may be performed.
[0055] [Electrochemical element] The present invention also includes an electrochemical element including the separator of the present invention. The separator of the present invention can be thinned while maintaining high strength, and therefore can improve the performance of the electrochemical element and reduce its size and weight without reducing the durability of the electrochemical element.
[0056] Examples of electrochemical elements include electric double layer capacitors, lithium ion capacitors, aluminum electrolytic capacitors, lithium ion secondary batteries, sodium ion secondary batteries, sodium sulfur secondary batteries, etc. Among these electrochemical elements, the separator of the present invention is suitable for capacitors such as electric double layer capacitors and lithium ion capacitors.
[0057] The electrochemical element of the present invention includes a positive electrode, a negative electrode, and an electrolyte in addition to the separator of the present invention. The positive electrode and the negative electrode included in the electrochemical element are not particularly limited, and may be, for example, a known positive electrode and a negative electrode used in an electrochemical element. The electrolyte is also not particularly limited, and may be, for example, an organic electrolyte (non-aqueous electrolyte). The organic electrolyte may be, for example, a mixture of tetraalkylammonium cation and BF 4 - , P.F. 6 - , S.O. 3 CF 3 - Examples of the electrolyte include an electrolyte in which a salt with an anion such as the above is dissolved in an organic solvent such as propylene carbonate or ethylene carbonate.
[0058] The shape of the separator in the electrochemical element is not particularly limited, and examples thereof include cross strip (cylindrical cross structure with a bottom), round strip (cylindrical roll), and spiral (spiral roll structure).
[0059] The method for producing the electrochemical element is not particularly limited, and the element can be produced according to a conventionally known method. EXAMPLES
[0060] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0061] The physical properties of the beaten cellulose fibers were measured and evaluated by the methods described below. [Freeness of beaten cellulose fibers] The Canadian standard freeness was measured according to JIS P-8121 (Testing method for freeness of pulp) using a Canadian standard freeness tester (manufactured by Kumagai Riki Kogyo Co., Ltd., "Canadian Freeness Tester").
[0062] [Fiber diameter and fiber diameter distribution of beaten cellulose fibers] (1) Number average fiber diameter and maximum fiber diameter 100 g of beaten cellulose fiber was dispersed in 10 L of water to prepare a slurry. The fiber diameter of the beaten cellulose fiber was measured using the obtained slurry under the following conditions with a "Fiber Tester" manufactured by Lorentzen & Wettre. Measurement conditions: Mode: Auto mode Data range (fiber diameter range): 0 to 100 μm Class width: 2 The number average fiber diameter and maximum fiber diameter of the beaten cellulose fibers were calculated from the fiber diameter data obtained by the measurement. The results are shown in Table 1. (2) The maximum frequency peak in the fiber diameter distribution histogram Using the fiber diameter data of the beaten cellulose fibers obtained by the measurement in (1) above, a fiber diameter distribution histogram (class width: 2) of the beaten cellulose fibers was created. The fiber diameter distribution histograms of the beaten cellulose fibers with each freeness are shown in Figures 1 to 7. Note that the fiber diameter on the horizontal axis in the figures represents the lower limit fiber diameter in each class (for example, 20 μm on the horizontal axis represents a class of fiber diameters of 20 μm or more and less than 22 μm). In the fiber diameter distribution histogram of the beaten cellulose fiber thus prepared, the most frequent class was adopted as the maximum frequency peak. Table 1 shows the fiber diameter at the maximum frequency peak. The fiber diameter at the maximum frequency peak was taken as the lower limit fiber diameter of the most frequent class. For example, when the most frequent class was 18 μm or more and less than 20 μm, the fiber diameter at the maximum frequency peak was taken as 18 μm. (3) The proportion of fibers with a specific fiber diameter in the fiber diameter distribution histogram In the beaten cellulose fibers, the respective proportions of fibers having a fiber diameter of 20 μm or less, 30 μm or less, and more than 30 μm were calculated from the histogram by determining the sum of the frequencies of all classes (all data intervals) (total frequency), the sum of the frequencies from the class including the minimum fiber diameter to the class of 20 μm or more and less than 22 μm (total frequency of 20 μm or less), the sum of the frequencies from the class including the minimum fiber diameter to the class of 30 μm or more and less than 32 μm (total frequency of 30 μm or less), and the sum of the frequencies from the class of 32 μm or more and less than 34 μm to the class including the maximum fiber diameter (total frequency of more than 30 μm), and using the following formula. Percentage of fibers with a diameter of 20 μm or less = (total frequency of fibers with a diameter of 20 μm or less / total frequency) x 100 Percentage of fibers with a fiber diameter of 30 μm or less = (total frequency of fibers with a diameter of 30 μm or less / total frequency) x 100 Percentage of fibers with a diameter of 30 μm or more = (total frequency of fibers with a diameter of 30 μm or more / total frequency) × 100
[0063] The physical properties of the separators obtained in the examples and comparative examples were measured by the methods described below. The measurement results are shown in Table 1.
[0064] [Metsuke] Measurements were made in accordance with JIS P 8124 (method of measuring metric basis weight of paper).
[0065] [Thickness] Measurements were made in accordance with JIS P 8118 (Testing methods for thickness and density of paper and paperboard).
[0066] [Strong] The measurements were carried out according to JIS P-8113 (Paper and paperboard-Testing methods for tensile properties) using a tensile tester (Instron Corporation, "5543").
[0067] [Breathability] The measurement was carried out according to JIS L 1096 6.27 (General fabric testing method: Air permeability) using an air permeability tester (manufactured by Kato Tech Co., Ltd., "KES-F8-AP1").
[0068] [Resistance value] The resistance values of the separators obtained in the examples and comparative examples were measured in auto mode using a resistance measuring device (Kokuyo Electric Industries Co., Ltd., "KC-547 LCR METER"). Specifically, five separators obtained in the examples and comparative examples were stacked to prepare a resistance measuring sample, and the resistance measuring sample was immersed in an electrolyte (Toyama Pharmaceutical Co., Ltd., capacitor reagent "Electrolyte CAPASTE") for one hour, and then the resistance measuring sample was taken out of the electrolyte, and the resistance measuring sample was sandwiched between platinum from above and below, and the above device was used to measure the resistance.
[0069] Example 1 Natural cellulose fibers (mercerized wood pulp) (minimum fiber diameter: 5 μm, maximum fiber diameter: 70 μm) were beaten using a refiner (Kumagaya Riki Kogyo Co., Ltd., "Test Niagara Beater") in accordance with JIS P-8221-1-98 (Pulp - Beating method - Part 1: Beater method) to obtain beaten cellulose fibers with a freeness of 150 ml. The obtained natural cellulose fiber with a freeness of 150 ml was dispersed in water at 75% by mass, 0.3 dtex × 3 mm polyvinyl alcohol-based fiber (Kuraray Co., Ltd., Vinylon, VN30300) at 20% by mass, and 1.1 dtex × 3 mm polyvinyl alcohol-based binder (Kuraray Co., Ltd., Vinylon binder: VPB107-1 × 3) at 5% by mass to produce a slurry (total mass of synthetic fiber, beaten cellulose fiber, and binder: water = 100 g: 10 L). A two-layered paper was made using a papermaking machine (Kumagaya Riki Kogyo Co., Ltd., "Square sheet machine (25 cm square)") according to JIS P-8222 (Pulp - Preparation method of hand-made paper for testing). The paper was dried at 120 ° C for 1 minute with an input moisture of 70% using a rotary dryer (Kumagaya Riki Kogyo Co., Ltd., "Rotary dryer DR-200"), and the basis weight was 20 g / m. 2 Thus, a separator for an electric double layer capacitor (EDLC) having a thickness of 48 μm was obtained.
[0070] Example 2 The same procedure as in Example 1 was repeated except that the freeness of the beaten cellulose fiber was adjusted to 250 ml, and the basis weight was 20 g / m 2Thus, a separator for EDLC having a thickness of 50 μm was obtained.
[0071] Example 3 The same procedure as in Example 1 was repeated except that the freeness of the beaten cellulose fiber was adjusted to 350 ml, and the basis weight was 20 g / m. 2 Thus, a separator for EDLC having a thickness of 52 μm was obtained.
[0072] Example 4 A woven fabric having a basis weight of 20 g / m was prepared in the same manner as in Example 1, except that the freeness of the beaten cellulose fiber was adjusted to 250 ml, the blending amount of the beaten cellulose fiber was changed to 77.5% by mass, and the blending amount of the polyvinyl alcohol binder was changed to 2.5% by mass. 2 Thus, a separator for EDLC having a thickness of 51 μm was obtained.
[0073] Example 5 A woven fabric having a basis weight of 20 g / m was prepared in the same manner as in Example 1, except that the freeness of the beaten cellulose fiber was adjusted to 250 ml, the blending amount of the beaten cellulose fiber was changed to 79.5% by mass, and the blending amount of the polyvinyl alcohol binder was changed to 0.5% by mass. 2 Thus, a separator for EDLC having a thickness of 52 μm was obtained.
[0074] Example 6 Weight: 18g / m 2 The same procedure as in Example 2 was repeated except that the weight was adjusted to 18 g / m 2 Thus, a separator for EDLC having a thickness of 45 μm was obtained.
[0075] Example 7 Weight: 18g / m 2 The same procedure as in Example 3 was repeated except that the weight was adjusted to 18 g / m 2 Thus, a separator for EDLC having a thickness of 46 μm was obtained.
[0076] Example 8 A spun spun spun spun spun spun spun with a basis weight of 20 g / m was prepared in the same manner as in Example 1, except that a 0.4 dtex × 3 mm polyester fiber (Kuraray Co., Ltd., polyester, EP043) was used as the synthetic fiber instead of the polyvinyl alcohol fiber. 2Thus, a separator for EDLC having a thickness of 50 μm was obtained.
[0077] Example 9 A fabric having a basis weight of 20 g / m was prepared in the same manner as in Example 1, except that the blending amount of beaten cellulose fiber was changed to 40% by mass and the blending amount of polyvinyl alcohol-based fiber was changed to 55% by mass. 2 Thus, a separator for EDLC having a thickness of 53 μm was obtained.
[0078] Example 10 A fabric having a basis weight of 20 g / m was prepared in the same manner as in Example 1, except that the blending amount of beaten cellulose fiber was changed to 90% by mass and the blending amount of polyvinyl alcohol-based fiber was changed to 5% by mass. 2 Thus, a separator for EDLC having a thickness of 46 μm was obtained.
[0079] Example 11 Weight: 15g / m 2 The same procedure as in Example 1 was repeated except that the weight was adjusted to 15 g / m 2 Thus, a separator for EDLC having a thickness of 42 μm was obtained.
[0080] Comparative Example 1 The same procedure as in Example 1 was repeated except that the freeness of the beaten cellulose fiber was adjusted to 25 ml, and the basis weight was 20 g / m 2 Thus, a separator for EDLC having a thickness of 41 μm was obtained.
[0081] Comparative Example 2 The same procedure as in Example 1 was repeated except that the freeness of the beaten cellulose fiber was adjusted to 550 ml, and the basis weight was 20 g / m 2 Thus, a separator for EDLC having a thickness of 55 μm was obtained.
[0082] Comparative Example 3 Organic solvent-based cellulose fiber "Lyocell" (Lenzing Co., Ltd., "Lyocell") was beaten in the same manner as in Example 1, and 100% by mass of the beaten cellulose fiber adjusted to a freeness of 50 ml was dispersed in water to produce a slurry (beaten cellulose fiber: water = 100 g: 10 L). Papermaking and drying were then carried out in the same manner as in Example 1, and a basis weight of 20 g / m was obtained. 2 Thus, a separator for EDLC having a thickness of 55 μm was obtained.
[0083] Comparative Example 4 Weight: 17g / m 2 The same procedure as in Comparative Example 3 was repeated except that the weight was adjusted to 17 g / m 2 Thus, a separator for EDLC having a thickness of 50 μm was obtained.
[0084] Comparative Example 5 Weight: 15g / m 2 The same procedure as in Comparative Example 3 was repeated except that the weight was adjusted to 15 g / m 2 Thus, a separator for EDLC having a thickness of 45 μm was obtained.
[0085] Comparative Example 6 The same procedure as in Comparative Example 3 was repeated except that the freeness of the organic solvent-based cellulose fiber was adjusted to 250 ml, and the basis weight was 20 g / m 2 Thus, a separator for EDLC having a thickness of 59 μm was obtained.
[0086] [Table 1]
[0087] As shown in Table 1, it was confirmed that the separators obtained in Examples 1 to 11 had high strength even though they were thin. Furthermore, the separators obtained in Examples 1 to 11 showed low resistance values. In contrast, in Comparative Examples 2 to 6, separators that were thin and had high strength were not obtained. Furthermore, the separators obtained in Comparative Examples 1 and 3 had high resistance values and were not suitable as separators for electrochemical elements. Moreover, the separator obtained in Comparative Example 2 had high air permeability and insufficient shielding properties.
Claims
1. A separator for an electrochemical element comprising synthetic fibers and beaten cellulose fibers, The Canadian standard freeness of the beaten cellulose fiber measured in accordance with JIS P 8121 is 50 ml or more and 500 ml or less; In the fiber diameter distribution histogram of the beaten cellulose fiber, (1) the fiber has a maximum frequency peak in the range of 50 μm or less; (2) The proportion of the fibers having a fiber diameter of 20 μm or less is 55% or more; Separator for electrochemical elements.
2. The separator for an electrochemical element according to claim 1 , further comprising a binder.
3. 3. The separator for an electrochemical element according to claim 1, wherein in a fiber diameter distribution histogram of the beaten cellulose fibers, the proportion of said fibers having a fiber diameter of more than 30 μm is 10% or less.
4. 4. The separator for an electrochemical element according to claim 1, wherein the synthetic fiber is a polyvinyl alcohol-based fiber and / or a polyester-based fiber.
5. 5. The separator for an electrochemical element according to claim 1, wherein the beaten cellulose fibers are natural cellulose fibers that have been beaten.
6. 6. The separator for an electrochemical element according to claim 2, wherein the binder is a polyvinyl alcohol-based binder.
7. 7. The separator for an electrochemical element according to claim 1, wherein the content of the synthetic fiber is 1% by mass or more and 55% by mass or less based on the total mass of the separator.
8. 8. The separator for an electrochemical element according to claim 1, wherein the content of the beaten cellulose fibers is 30% by mass or more and 95% by mass or less based on the total mass of the separator.
9. 9. The separator for an electrochemical element according to claim 2, wherein the content of the binder is 0.5% by mass or more and 20% by mass or less with respect to the total mass of the separator.
10. The separator for an electrochemical element according to any one of claims 1 to 9, which has a thickness of 10 µm or more and less than 70 µm.
11. An electrochemical element comprising the separator for electrochemical elements according to any one of claims 1 to 10.
Citation Information
Patent Citations
Separator for electrochemical element and electrochemical element using the same
JP2012222266A